Industrial agglomeration in Myanmar - John Rand; Finn Tarp; Neda Trifkovic; Helge Zille (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Focusing on labour productivity and working conditions, we investigate the benefits of industrial zones for private manufacturing enterprises in Myanmar. We find that being located in an industrial zone associates with higher labour productivity. Value added gains, however, are not transferred to employees. The results are robust to different measures of productivity and model specifications, as well as to controlling for the natural level of industrial agglomeration in a particular location. The findings in general indicate additional benefits of planned industrial activities as opposed to naturally driven industrial clustering.
Keywords: D24; L25; R12; J31; J81; 330; agglomeration; industrial zones; labour; Myanmar; productivity